2016
DOI: 10.1016/j.ssresearch.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of parental labor migration in China for children's emotional wellbeing

Abstract: Using data from the 2010 wave of the China Family Panel Studies (CFPS), we study the effects of internal migration in China on the emotional well-being of children age 10-15. The 2010 CFPS, a national probability sample survey of the Chinese population, includes 3,464 children within this age range. We compare five groups: rural children with local registration living with both parents; urban children with local registration living with both parents; children accompanying their migrant parent(s); children left… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 53 publications
1
67
0
Order By: Relevance
“…These concerns likely affect whether migrant parents bring their children with them or not (Xu and Xie 2013). Second, while we have only been able to examine one important aspect of child development, i.e., school enrollment, migration and separation from parents may have profound implications for other aspects such as children's academic performance, psychological well-being, behaviors and their development of non-cognitive skills (Lu and Zhou 2013;Ren and Treiman 2013), all of which are as important as schooling in determining their future labor productivity and status attainment in destination cities. Finally, sociologists argue that the negative consequences of migration on children's schooling are due to the loss of social capital in school, the neighborhood, and the community of origin (Astone and Mclanahan 1994;Buchmann and Hannum 2001;Loyd and Blanc 1996;Pribesh and Downey1999).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These concerns likely affect whether migrant parents bring their children with them or not (Xu and Xie 2013). Second, while we have only been able to examine one important aspect of child development, i.e., school enrollment, migration and separation from parents may have profound implications for other aspects such as children's academic performance, psychological well-being, behaviors and their development of non-cognitive skills (Lu and Zhou 2013;Ren and Treiman 2013), all of which are as important as schooling in determining their future labor productivity and status attainment in destination cities. Finally, sociologists argue that the negative consequences of migration on children's schooling are due to the loss of social capital in school, the neighborhood, and the community of origin (Astone and Mclanahan 1994;Buchmann and Hannum 2001;Loyd and Blanc 1996;Pribesh and Downey1999).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This suggests that parents' migration could have a positive effect on children's schooling by providing the necessary economic resources. But their absence could have a negative impact as a result of the loss of social capital and parental attention (Chang, Dong and MacPhail 2011;Ren and Treiman 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The mere presence of parents at home offers companionship and support could make children more productive in school. Some research has shown that children with strong parental support do well in school and develop strong non-cognitive skills (Ren and Treiman 2016). Parental presence can contribute to children's school performance in the role of supervision and monitoring to ensure their children finish homework assignments each day and to make up for missed classes.…”
Section: How Return Migrant Parents May Affect Children's School Perfmentioning
confidence: 99%
“…Children's personality, mental and physical health, learning habits and daily behaviors were followed and measured over certain periods. CFPS provided unified math, language and psychological tests to measure children's educational performance and psychological wellbeing [67] [115].…”
Section: Quantitative Datamentioning
confidence: 99%